2021
DOI: 10.18592/tarbiyah.v10i1.4113
|View full text |Cite
|
Sign up to set email alerts
|

Student's Perspective on Virtual Laboratory Using Phet as A Media in Conducting Physics Laboratory Activities

Abstract: The purpose of writing this paper article is to review students' perceptions in the use of PhET-based virtual labs and also to provide a description in comparison to perceptions of virtual lab use from some of the results of previous studies that are relevant to this study. There are five aspects in the perception that will be surveyed, including; (1) aspects of innovation, (2) aspects of benefits (3) aspects of motivation, (4) aspects of effectiveness, (5) aspects of presenting procedures for laboratory activ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 17 publications
0
6
0
2
Order By: Relevance
“…Sulistiowati, in her research, found that students' interest in laboratory activities was very high by showed high interest in learning and understanding after using real and virtual laboratories (Sulistiowati et al 2013). This laboratory activity can facilitate the process of transferring knowledge from educators to students, as in Putra's (RP Putra et al 2021) research, he found that 78.4% of the subjects he studied in semesters 2 to 6 students regarding their views on the use of virtual laboratories in learning were felt to be very necessary because apart from just theory, Virtual and actual laboratory activities are needed to describe the theory being studied.…”
Section: Introductionmentioning
confidence: 93%
“…Sulistiowati, in her research, found that students' interest in laboratory activities was very high by showed high interest in learning and understanding after using real and virtual laboratories (Sulistiowati et al 2013). This laboratory activity can facilitate the process of transferring knowledge from educators to students, as in Putra's (RP Putra et al 2021) research, he found that 78.4% of the subjects he studied in semesters 2 to 6 students regarding their views on the use of virtual laboratories in learning were felt to be very necessary because apart from just theory, Virtual and actual laboratory activities are needed to describe the theory being studied.…”
Section: Introductionmentioning
confidence: 93%
“…Terlebih lagi simulasi ini akan membantu siswa memahami konsep abstrak jika nanti digunakan oleh guru di kelas, efektif dan efisien digunakan di kelas untuk menggantikan praktikum nyata, dan meningkatkan hasil belajar (Banda & Nzabahimana, 2022;Putra & Anjani, 2022). Simulasi PhET juga dapat menjadikan siswa antusias belajar sehingga kemampuan kognitif meningkat (Martanti et al, 2021;Puspita, 2021;Putra & Anjani, 2022). Siswa antusias karena tampilan dari simulasi PhET menarik (Serevina et al, 2021;Suryanto et al, 2021).…”
Section: Gambar 5 Pemaparan Materi Tentang Simulasi Phet Dan Mahasisw...unclassified
“…lectures without having to interfere with other activities between the lecturers or undergraduate students, and also the use of technology that they just find useful. Efficiency and time flexibility in online lectures are felt to be very high because lecturers or students in implementing their online lectures can manage their time by mutual agreement (Hamid et al, 2020), besides that the use of technology in online lectures is felt to have a positive impact on undergraduate students who carry out online lectures, where many undergraduate students experience the use of new technology (Putra et al, 2021). In contrast, the PoC19S population, where they do not feel happy when carrying out lectures offline because they are used to online lectures which are felt to be effective and time efficient, so they can spend more time outside of lectures, as statements from various subjects stated that they are more interested in student organization activities than lecture activities, and not a few of them ask for offline lectures to be online because they want to carry out student organization activities offline.…”
Section: Enjoymentmentioning
confidence: 99%